(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
The corrosion of reinforcement in reinforced concrete (RC) structures is a major concern for their durability and long-term performance. In recent years, the use of Fiber Reinforced Polymer (FRP) wrapping has gained significant attention as an effective corrosion protection strategy. However, it is crucial to monitor the condition of the FRP wrapping and its ability to provide ongoing protection against corrosion. Guided wave-based monitoring techniques have emerged as a promising approach for assessing the integrity and corrosion resistance of FRP-wrapped RC structures. This literature review provides an overview of the research conducted on utilizing guided waves for monitoring the corrosion protection of RC structures with active FRP wrapping. The review focuses on various aspects including the principles of guided wave propagation, experimental methods employed for monitoring, signal analysis techniques, and case studies of practical applications. The review reveals that guided wave-based monitoring offers several advantages, such as its non-destructive nature, ability to cover large areas, and sensitivity to both localized and distributed corrosion damage. Various guided wave modes, such as Lamb waves and torsional waves, have been investigated for detecting corrosion-related defects in FRP-wrapped RC structures. Signal processing techniques, such as wavelet transforms and time-frequency analysis, have been employed to enhance defect detection and localization. The case studies demonstrate the effectiveness of guided wave-based monitoring in detecting corrosion initiation, progression, and its impact on the integrity of FRP-wrapped RC structures. The results highlight the potential of this monitoring technique in providing early warning signs of corrosion and enabling timely maintenance and repair interventions.